2017
DOI: 10.7897/2277-4343.083146
|View full text |Cite
|
Sign up to set email alerts
|

PHYTO-PHARMACOGNOSTICAL EVALUATION AND HPTLC STUDY ON ANANTAMUL (HEMIDESMUS INDICUS R.Br.) ROOT

Abstract: Plants are among the richest sources of bioactive compounds throughout the world for thousands of years and continue to provide new remedies to mankind. Roots of Hemidesmus indicus R. Br. is an important plant drug which is used to cure leprosy, leucoderma, itching, skin disease, asthma, bronchitis, leucorrhoea, dysentery, piles, syphilis, paralysis, urinary disorders and diabetics. The present study focused on the pharmacognostical, phytochemical investigation as well as HPTLC study on Hemidesmus indicus root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Phalsa pomace's flavonoid concentration was estimated to be 12.42056 CE mg/g [36,37]; it was found that the rind/bark contained 39.114 ± 65 mg of flavonoids. The results of another investigation showed that the fruit's solvent extract's total flavonoid concentration and phenolic content were, respectively, 0.13 and 5.25 GAE/mL [38]. The bioactive potential of various parts of berry trees is given in detail in Table 2.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Phalsa pomace's flavonoid concentration was estimated to be 12.42056 CE mg/g [36,37]; it was found that the rind/bark contained 39.114 ± 65 mg of flavonoids. The results of another investigation showed that the fruit's solvent extract's total flavonoid concentration and phenolic content were, respectively, 0.13 and 5.25 GAE/mL [38]. The bioactive potential of various parts of berry trees is given in detail in Table 2.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The use of herbal drugs is rapidly increasing worldwide as the herbal drugs were found to be beneficial in treating mild to moderate diseases in all age groups and in averting illnesses thereby promoting health (2). Roots of H. indicus is an important plant drug used as a tonic, demulcent, diaphoretic and diuretic as per Siddha literature, it is used to treat a variety of diseases such as leprosy, leucoderma, itching, skin disease, body coolant, asthma, bronchitis, leucorrhoea, dysentery, piles, syphilis, paralysis, urinary disorders and diabetes (3). Hemidesmus indicus (L.) R. Br.…”
Section: Introductionmentioning
confidence: 99%